Analisis Kemenangan Pasangan Calon Andra Soni dan Dimyati Natakusumah dalam Pilgub Banten 2024 - Iqbal, Ighasta Ahmad; Putriesli, Lamona; Salsabila, Nasywa; Putranto, Algooth (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The Andra-Dimyati pair built a large coalition with the support of ten political parties, demonstrating significant electoral strength in the Banten gubernatorial election. Their vision and mission, which focuses on "Banten Maju, Adil Merata tidak Korupsi" (Advanced, Fair, Equitable, No Corruption), includes priority programs such as improving workers' welfare, free education for high school students, and increasing village budgets. These programs are expected to be able to answer the needs of the community, especially the younger generation and labor groups. The campaign strategy that utilizes social media, especially Instagram and TikTok, allows them to reach young voters with dynamic and interactive visual content. Through live streaming, Instagram Stories, and entertainment-based content, they have succeeded in creating direct interaction and strengthening closeness with voters. An innovative approach to social media campaigns and strong coalition support increase Andra-Dimyati's competitiveness in the 2024 Banten gubernatorial election.